Caste or colony ? Indianizing race in the United States - daniel immerwahr (Modern Intellectual History, 4, 2 (2007), pp. 275-301, 2007)
Since the 1830s thinkers in both the United States and India have sought to establish analogies between their respective countries. Although many have felt the US black experience to have obvious parallels in India, there has been a fundamental disagreement about whether being black is comparable to being colonized or to being untouchable. By examining these two competing visions, this essay introduces new topics to the study of black internationalism, including the caste school of race relations, B. R. Ambedkar's anti-caste movement, and the changing significance of India for Martin Luther King, Jr.